SISTEM INFORMASI PENGELOLAAN PUSAT PRESTASI MAHASISWA GUNA MENDUKUNG PROGRAM KREATIFITAS MAHASISWA - Marlya Fatira AK; Safaruddin Safaruddin; Habibi Ramdani Safitri (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
The student activity information system is one of the digital tools needed to facilitate and bridge the needs of students in the non-academic field. This is done to support the active participation of students in achieving non-academic achievements in the campus environment. This study uses secondary data and primary data. Secondary data is obtained in the form of student data that actively participate in non-academic activities that support achievement. Primary data was collected from interviews. This is to get data about the condition of student achievement management in the Medan State Polytechnic. Data analysis techniques were carried out using qualitative methods, and then a website was launched to facilitate the need for information systems in providing services to students for academic and non-academic achievement through the student achievement center. The results showed that after designing an information system through the student achievement center website, it was known that the initial response of students to use was easy and interested in using the website to view information and follow various published information, including active roles in assisting the student directorate for student achievement—both academic and non-academic for the maximum achievement of the main performance indicator targets for Medan State Polytechnic.